2016
DOI: 10.1016/j.apcata.2016.02.032
|View full text |Cite|
|
Sign up to set email alerts
|

Esterification of levulinic acid with butanol over ion exchange resins

Abstract: Alkyl levulinates are biobased chemicals with a great number of applications and great biofuel potential for blending to conventional diesel or gasoline. The present work focuses on the liquid-phase synthesis of butyl levulinate (BL) by esterification of levulinic acid (LA) with 1-butanol (BuOH) using a set of acidic ion-exchange resins. Experiments were performed at 80ºC and 2.5 MPa in a batch reactor by using an initial molar ratio AL/BuOH of 1/3 and a catalyst loading of 0.8%. It has been found that BL coul… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
58
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 105 publications
(59 citation statements)
references
References 68 publications
1
58
0
Order By: Relevance
“…Despite encouraging literature precedents [22,33], Amberlyst 15 gave only 52% conversion of 1 within 2 h (Table 1, entry 5, 31% yield). We then switched to perfluorinated resins.…”
Section: Resultsmentioning
confidence: 90%
See 1 more Smart Citation
“…Despite encouraging literature precedents [22,33], Amberlyst 15 gave only 52% conversion of 1 within 2 h (Table 1, entry 5, 31% yield). We then switched to perfluorinated resins.…”
Section: Resultsmentioning
confidence: 90%
“…Although the behaviour of many metal oxides has been investigated, reports featuring the activity of supported organic Brønsted acids are very few. In particular, Tejero reported that sulfonic acid supported on polymeric resins could catalyse the esterification of LA, providing conversions up to 94% upon warming at 80 °C for 8 hours in the presence of 3 equiv of n -butanol [33]. Melero described the synthesis of mesostructured silica frameworks featuring pending organosulfonic arms.…”
Section: Introductionmentioning
confidence: 99%
“…A resins screening among several macroreticular and gel‐type resins with different crosslinking degree and sulfonation procedure (Amberlyst‐15, ‐16, ‐35, ‐36, ‐39, ‐46, ‐70, Purolite CT‐224, Dowex 50Wx2, x4, x8) was carried out in order to select suitable catalyst for obtaining BL and to find a possible effect of resins morphology on the catalytic activity. At 353 K and 2.5 MPa with a slight alcohol excess, BL was successfully obtained with selectivity higher than 99.5% for all the resins . By comparing the catalytic behavior, it was seen that resins morphology plays a very important role in BL synthesis.…”
Section: Production Of Levulinic Acidmentioning
confidence: 92%
“…A very recent paper of our group was devoted to the study of the synthesis of BL over sulfonated resins. 69 A resins screening among several macroreticular and gel-type resins with different crosslinking degree and sulfonation procedure (Amberlyst-15, -16, -35, -36, -39, -46, -70, Purolite CT-224, Dowex 50Wx2, x4, x8) was carried out in order to select suitable catalyst for obtaining BL and to find a possible effect of resins morphology on the catalytic activity. At 353 K and 2.5 MPa with a slight alcohol excess, BL was successfully obtained with selectivity higher than 99.5% for all the resins.…”
Section: A-36 + Olefinsmentioning
confidence: 99%
“…However, the literature on the synthesis of BL via the esterification of LA are sparse. Several types of solid acids such as supported montmorillonite [21], zeolites [22,23], metal-organic frameworks [24], Al-MCM-41 [25], ion-exchange resins [26,27], graphene oxide [28] and immobilized lipase [29] have been utilized in the esterification of LA with n-butanol. Surprisingly, the catalysis with amorphous carbon materials to produce BL has not been explored before.…”
Section: Introductionmentioning
confidence: 99%